Tourism information system - Aida Zuraina, Mir Ahmad Talaat (2005)
Tourist Information Centre (TIC) is an information centre for tourist either from Malaysia or other country. TIC still implementing the manual system to store data.All the data were kept either in the log book, template or brochure. This manual system will encouter many problems to the TIC staffs such as in updating and searching the data.It will become a big problem where some of the data might be loss during the operation.The exact data and information could not be delivered to the tourist because of the problems that occured. Therefore, the Tourism Information System (TIS) is suggested to solve the problem. TIS consists of three (3) modules.The modules are location module, accommodation module and transportation module.The Searching Technique which is Concept Mapping will be applied in order to search and retrieve the data in the database. At the end of the project, a prototype of TIS is developed where it will be able to keep and save all Tourist Information Centre (TIC) data in the database.This will makes the data more manageable and systematic.